Polyamine Metabolism, Photorespiration, and Excitation Energy Allocation in Photosystem II Are Potentially Regulatory Hubs in Poplar Adaptation to Soil Nitrogen Availability - Hu, Yanbo; Siddiqui, Manzer H.; Li, Chunming; Jiang, Luping; Zhang, Heng; Zhao, Xiyang (Frontiers in Plant Science, 2020)
Poplar growth (leaf area) and N utilization significantly increased under fertilized compared to unfertilized conditions; whereas photosynthetic N utilization efficiency significantly decreased under low N supplies. Growth characteristics were better in XQH than BC5 clone under the same N supplies, indicating a higher N utilization efficiency. Leaf absorbed light energy and thermal dissipation fraction were significantly different for XQH clone between conventional and exponential N additions. Leaf concentrations of putrescine (Put) and acetylated Put were significantly higher in exponential than conventional N addition. Photorespiration significantly increased in leaves of XQH clone under exponential compared to conventional N addition. Our results indicate that an interaction of the clone and N supply pattern significantly occurs in poplar growth; leaf expansion and the storage N allocations are the central hubs in regulation of poplar N utilization.